The Relationship of Consumer Ethnocentrism, Purchase Intention, and Lifestyle in First-generation Bicultural Ethnic Groups - Aguilar Rodríguez, Iliana Elizabeth (2021)
This study analyzed the relationship between first-generation Colombian – Canadian bicultural ethnic consumers, their purchase intention, and lifestyles. These common types of consumers were to make purchases depending on the lifestyle, bicultural ethnic group, and the ethnocentric trends that might differ from the country of origin or the host country. There were 158 surveys administered in Toronto, Canada. Structural Equation Modeling was applied, using the Unweighted Least Squares Estimates and Maximum Likelihood Methods. An Exploratory Factor Analysis was run using the principal axis method and Promax rotation after conducting the multivariate normality tests, reliability, and discriminant and convergent validity tests. The Confirmatory Factor Analysis guaranteed an adequate measurement model. The purchase intention was explained as 85.2% for lifestyle factors, such as self-reliance and leadership, nurturing and family orientation, household oriented and industrious, and ethnocentrism in Colombia and Canada. It was found that lifestyle factors were not significantly related to purchase intention. However, ethnocentrism positively impacted Canadian product perceptions and a negative impact on Colombian products. Results showed that lifestyles (activities, interests, and opinions [AIO]) are not always key elements in consumer’s purchase intentions. Bicultural consumer ethnocentric trends are stronger in the host country because consumers in a developing country accept more developed countries. The study supported the theory of social identity (Tajfel, 1982) and optimal distinction (Brewer, 1979), which suggests consumers would have a bias towards the country with which they identify or experience dual or divided loyalties between the country of origin and the host country.